Problems and directions of integration of Russia into international transport systems - Golubchik, Andrej Moiseevich; Kholopov, Konstantin Vladimirovich (Российский внешнеэкономический вестник, 2024)
The authors define the value of transport systems as an effective integrator of the countries and regions in the international economy. They also consider primary goals of transport for achievement of the purposes of the international economic integration, priorities of participation of Russia in transport projects on the post-Soviet territory, and prove the necessity of participation for the international transport organizations. The purposes and problems of functioning of the international transport corridors on the Russian territory are considered in detail.